2011
DOI: 10.1021/ic200154y
|View full text |Cite
|
Sign up to set email alerts
|

Using the Outer Coordination Sphere to Tune the Strength of Metal Extractants

Abstract: A series of 3-substituted salicylaldoximes has been used to demonstrate the importance of outer-sphere interactions on the efficacy of solvent extractants that are used to produce approximately one-quarter of the world's copper. The distribution coefficient for extraction of copper by 5-tert-butyl-3-X-salicylaldoximes (X = H, Me, (t)Bu, NO(2), Cl, Br, OMe) varies by more than two orders of magnitude. X-ray structure determinations of preorganized free ligand dimers (10 new structures are reported) indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…The bond distances subtended at the Cu atom are comparable to those observed in the similar copper(II) complexes with Schiff bases. 17,18 The morpholine rings adopt well-shaped chair conformation.…”
Section: Resultsmentioning
confidence: 99%
“…The bond distances subtended at the Cu atom are comparable to those observed in the similar copper(II) complexes with Schiff bases. 17,18 The morpholine rings adopt well-shaped chair conformation.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported previously that the X-substituent of the phenolic oxime buttressed the hydrogen-bonding interaction between the phenolic oxygen atom and the adjacent oxime hydrogen atom, and that the nature of the X-substituent was a dominant effect on the strength of solvent extraction of Cu ( Figure 4) [12,13]. This is perhaps, surprising, as the bond dissociation energies of metal-ligand bonds are at least one order of magnitude greater than those of hydrogen bonds.…”
Section: Complex Formationmentioning
confidence: 88%
“…At pH 0, 30% of Cu(II) content was transferred from the methoxy group of HL3ox enters into weak hydrogen bond interaction with the oxime group of the neighboring molecule. 17,18 These weak hydrogen bond interactions are thought to contribute to the overall stability of the resulting complex. 17,18 When the extraction results are examined, it is found that HL1ox, HL2ox, and HL4ox have about 30% extraction capacities at pH 0, while HL3ox has about 55% extraction capacity.…”
Section: Solvent Extraction Studies Of Oxime Compoundsmentioning
confidence: 99%